2015
DOI: 10.3389/fnhum.2015.00560
|View full text |Cite
|
Sign up to set email alerts
|

Children’s belief- and desire-reasoning in the temporoparietal junction: evidence for specialization from functional near-infrared spectroscopy

Abstract: Behaviorally, children’s explicit theory of mind (ToM) proceeds in a progression of mental-state understandings: developmentally, children demonstrate accurate explicit desire-reasoning before accurate explicit belief-reasoning. Given its robust and cross-cultural nature, we hypothesize this progression may be paced in part by maturation/specialization of the brain. Neuroimaging research demonstrates that the right temporoparietal junction (TPJ) becomes increasingly selective for ToM reasoning as children age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Wiesmann and colleagues also demonstrated increased connectivity between temporoparietal and IFG regions in relation to ToM performance, suggesting both white matter maturation and increased connectivity strength across these classic ToM regions in preschool-aged children. Moreover, the progression from desire to belief reasoning being supported by the TPJ has recently been replicated using fNIRS methods (Bowman, Kovelman, Hu, & Wellman, 2015). On aggregate, these findings coalesce with electrophysiological evidence in dispelling the strict version of the ToM↔EF proposal of a completely overlapping neural network.…”
Section: Theory Of Mind Findingsmentioning
confidence: 73%
“…Wiesmann and colleagues also demonstrated increased connectivity between temporoparietal and IFG regions in relation to ToM performance, suggesting both white matter maturation and increased connectivity strength across these classic ToM regions in preschool-aged children. Moreover, the progression from desire to belief reasoning being supported by the TPJ has recently been replicated using fNIRS methods (Bowman, Kovelman, Hu, & Wellman, 2015). On aggregate, these findings coalesce with electrophysiological evidence in dispelling the strict version of the ToM↔EF proposal of a completely overlapping neural network.…”
Section: Theory Of Mind Findingsmentioning
confidence: 73%
“…The prediction that follows from this view is that the specialized functional organization for ToM would require substantial brain development and should not be present until approximately the time children are able to explain their FB understanding. However, other work using implicit measures such as eye gaze suggest that even infants and toddlers may track the mental states of others, including FBs, well before they can explain them (Baillargeon et al, 2010). Some interpret these findings as evidence of early present ToM (Leslie et al, 2004;Baillargeon et al, 2010;Carruthers, 2013).…”
Section: Significance Statementmentioning
confidence: 95%
“…However, other work using implicit measures such as eye gaze suggest that even infants and toddlers may track the mental states of others, including FBs, well before they can explain them (Baillargeon et al, 2010). Some interpret these findings as evidence of early present ToM (Leslie et al, 2004;Baillargeon et al, 2010;Carruthers, 2013). What develops under this view is not ToM specifically, but rather the general cognitive abilities that support the increasing verbal and cognitive demands of explicit tasks.…”
Section: Significance Statementmentioning
confidence: 97%
See 1 more Smart Citation
“…From the behavioral work alone it is clear that children increase in their ability to explicitly demonstrate understanding of others' beliefs in different tasks and across different situations (see Baillargeon et al 2010). Furthermore, previous work has shown that the TPJ continues to increase in specialization for processing others' beliefs into late childhood, and this brain development has been shown to be related to behavioral competency on explicit ToM tasks (Bowman et al 2015;Gweon et al 2012;Sabbagh et al 2009;Saxe et al 2009). Nevertheless, our results suggest that Functional organization for theory of mind in infants 28 a central component of the mature ToM network, the TPJ, spontaneously differentiates between the belief states of others' in infancy and this sensitivity is present well before the capacity to explicitly demonstrate ToM understanding develops.…”
Section: Functional Organization For Theory Of Mind In Infants 25mentioning
confidence: 99%